Dynamics of faecal shedding of ESBL- or AmpC-producing Escherichia coli on dairy farms - Hordijk, Joost (J Antimicrob Chemother, 2019)
OBJECTIVES: To explore the dynamics of faecal ESBL/AmpC shedding in dairy cattle and farmers, a study was conducted to examine changes in shedding by individual animals, as well as environmental exposure, and to study the association between antimicrobial use (AMU) and ESBL/AmpC shedding. METHODS: The study comprised a cross-sectional survey of 20 farms and a 1 year follow-up of 10 farms. Faecal samples were cultured by both direct inoculation on MacConkey agar + 1 mg/L cefotaxime (MC+) and enrichment in LB-broth + 1 mg/L cefotaxime with subsequent inoculation on MC+. Dust samples were collected using electrostatic dustfall collectors (EDCs). Human faecal samples were collected by the farmers. Presence of ESBL/AmpC genes was screened for by PCR and sequencing. Using mixed effects logistic regression, ORs were determined and population-attributable fractions (PAFs) calculated subsequently. RESULTS: In Phase 1, 8/20 farms were positive for ESBL/AmpC and, with 2 negative farms, were selected for Phase 2. Transient shedding of dominant allele variants was observed in the animals. EDCs and human faecal samples did not reflect what was observed in the animals. AMU was related to shedding of ESBLs in the next sampling moment [OR 14.6 (95% CI 3.0–80.0)] and the PAF of AMU was 0.36 (95% CI 0.08–0.77). Calves fed with colostrum from cows on dry-off therapy was not a risk factor [OR 1.7 (95% CI 0.7–4.9, P = 0.28)]. CONCLUSIONS: The presence of ESBL/AmpC could only be partly explained by AMU. No link was shown between shedding in cattle and humans or the environment. Interventions should focus on prevention of introduction.